2018
DOI: 10.1038/s41598-018-32754-y
|View full text |Cite
|
Sign up to set email alerts
|

NIR-II fluorescence imaging using indocyanine green nanoparticles

Abstract: Fluorescence imaging in the second near-infrared window (NIR-II) holds promise for real-time deep tissue imaging. In this work, we investigated the NIR-II fluorescence properties of a liposomal formulation of indocyanine green (ICG), a FDA-approved dye that was recently shown to exhibit NIR-II fluorescence. Fluorescence spectra of liposomal-ICG were collected in phosphate-buffered saline (PBS) and plasma. Imaging studies in an Intralipid® phantom were performed to determine penetration depth. In vivo imaging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 49 publications
3
87
0
Order By: Relevance
“…The fact that Cy5 performs this well may be related to its superior brightness relative to ICG caused by a different quantum yield. Optical imaging in the NIR range holds considerable promise due to reduced light scattering by the tissue and increased penetration depth when compared to the visible range [27].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that Cy5 performs this well may be related to its superior brightness relative to ICG caused by a different quantum yield. Optical imaging in the NIR range holds considerable promise due to reduced light scattering by the tissue and increased penetration depth when compared to the visible range [27].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical transformation of NIR-II imaging technology can be accelerated when ICG, an FDA approved imaging agent, is used. Later, the research team published another paper on NIR-II fluorescence imaging using indocyanine green nanoparticles (Bhavane et al, 2018). In this study, they collected the fluorescence spectra of ICG liposomes in PBS and plasma.…”
Section: Nanoparticles Based On Organic Fluorescent Dyesmentioning
confidence: 99%
“…NIR-II fluorescence imaging has received extensive attentions after the first use of in vivo NIR-II fluorescence imaging in mice in 2009. [3,26] Currently, various materials, such as carbon nanotubes, [20,27,28] quantum dots, [29][30][31][32] rare-earth nanoparticles, [33][34][35][36][37][38] organic small molecules, [39][40][41][42][43][44][45][46][47][48][49][50][51][52] and polymers, [53,54] have been applied in NIR-II fluorescence bioimaging. Although several reviews of NIR-II fluorescence probe for bio medical imaging have been reported, [3,6,11,15,18,24,55,56] currently no review article focuses on activatable NIR-II fluorescence probes since the first activatable NIR-II fluorescence probe was reported in 2013.…”
Section: "Always On" Versus Activatable Fluorescence Probesmentioning
confidence: 99%